Abingdon New Testament commentaries: Jude, 2 Peter - Kraftchick, Steven John (Nashville, TN : Abingdon Press, 2002)
"These commentaries are written with special attention to the needs and interests of theological students, but they will also be useful for students in upper-level college or university settings, as well as for pastors and other religious leaders. In addition to providing basic information about the New Testament texts and insights into their meanings, these commentaries are intended to exemplify the task and procedures of careful, critical biblical exegesis." "In this volume Steven J. Kraftchick studies these two epistles in their late first century context and discusses their relevance to the contemporary Christian church. He discusses the importance of the insider/outsider language, the harsh polemical tone of both letters, and their reliance upon the Old Testament and both early Jewish and Greco-Roman thought. Kraftchick enables modern readers to find contemporary relevance in these difficult, ancient texts."--BOOK JACKET
Includes bibliographical references (pages 181-186) and index
Keywords: Bible. -- Commentaries; Bible. -- Commentaries